Emended description of Gardnerella vaginalis and description of Gardnerella leopoldii sp. nov., Gardnerella piotii sp. nov. and Gardnerella swidsinskii sp. nov., with delineation of 13 genomic species within the genus Gardnerella. Issue 3 (16th January 2019) - Vaneechoutte, Mario; Guschin, Alexander; Van Simaey, Leen; Gansemans, Yannick; Van Nieuwerburgh, Filip; Cools, Piet
Abstract : Whole genome sequence analysis (digital DNA–DNA hybridization and average nucleotide identity) was carried out for 81 sequenced full genomes of the genus Gardnerella, including ten determined in this study, and indicated the existence of 13 genomic species, of which five consist of only one strain and of which only five contain more than four sequenced genomes. Furthermore, a collection of ten Gardnerella strains, representing the emended species G. vaginalis and the newly described species Gardnerella leopoldii, Gardnerella piotii and Gardnerella swidsinskii, was studied. Matrix-assisted laser desorption ionization time-of-flight MS analysis of the protein signatures identified specific peaks that can be used to differentiate these four species. Only strains of G. vaginalis produce β-galactosidase. We emend the description of G. vaginalis (type strain ATCC 14018 T =LMG 7832 T =CCUG 3717 T ) and describe the novel species Gardnerella leopoldii sp. nov. (UGent 06.41 T =LMG 30814 T =CCUG 72425 T ), Gardnerella piotii sp. nov. (UGent 18.01 T =LMG 30818 T =CCUG 72427 T ) and Gardnerella swidsinskii sp. nov. (GS 9838-1 T =LMG 30812 T =CCUG 72429 T ).